1998
DOI: 10.1111/j.1439-0418.1998.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Beauveria bassiana (Balsamo) Vuillemin isolates for control of stored‐grain pests

Abstract: Seventy two isolates of Beauveria bassiana or Metarhizium anisopliae were screened for control of Sitophilus oryzae, S. zeamais (Col., Curculionidae), and Rhyzopertha dominica (Col., Bostrychidae). Beauveria bassiana isolates produced highest mortalities against all three hosts. Ten isolates (all B. bassiana) were selected for further experimentation in the second phase of selection process. Bioassays were conducted by inoculating 50 adult insects of each species, maintained at 26 OS'C, 70 f 10% RH, 12 h photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 7 publications
(2 reference statements)
1
36
0
2
Order By: Relevance
“…Alves et al (2002) observed mortality ranging from 43 to 78% of some isolates for B. bassiana on this spider mite. However, different isolates of the fungus exhibited a certain variability in pathogenicity and virulence toward different arthropods (Almeida et al, 1997;Moino et al, 1998). In our test, B. bassiana had a slight, positive effect on T. urticae fecundity, but reduced female and egg survival.…”
Section: Discussionmentioning
confidence: 78%
“…Alves et al (2002) observed mortality ranging from 43 to 78% of some isolates for B. bassiana on this spider mite. However, different isolates of the fungus exhibited a certain variability in pathogenicity and virulence toward different arthropods (Almeida et al, 1997;Moino et al, 1998). In our test, B. bassiana had a slight, positive effect on T. urticae fecundity, but reduced female and egg survival.…”
Section: Discussionmentioning
confidence: 78%
“…Na fase de screening é possível descartar materiais pouco virulentos e com baixa capacidade de penetração e germinação (Moino Jr. 1998). Assim, nesta primeira etapa optou-se pela seleção baseada na mortalidade confirmada (> 60%), eliminando-se os isolados com baixa esporulação.…”
Section: Resultsunclassified
“…The entomopathogenic fungus can diversify the production of virulence factors in response to the different insects (Moino et al, 1998). Inducer substrates have been tested in order to increase the protein content and to release the extracellular proteases to make easier the studies on kinetic activity and structure and to correlate with virulence levels of the fungal strain in bioassays on insects.…”
Section: Introductionmentioning
confidence: 99%